Removal of Cu2+ and Pb2+ ions by surfactant based cationic exchanger using cetylpyridinium chloride-cerium (IV) phosphate. Issue 42 (7th September 2016) - Iqbal, Nazia; Mobin, Mohammad; Rafiquee, M.Z.A.; Al-Lohedan, Hamad A.
Abstract: The surfactant-based organic–inorganic fibrous cation exchanger, cetylpyridinium chloride-cerium(IV) phosphate (CPC-CeP), has been synthesized and was characterized for its cationic exchange properties. The physicochemical methods such as Fourier transform infra-red spectroscopy (FTIR), X-ray diffraction pattern, scanning electron microscopy, thermogravimetric and differential thermogravimetric analysis (TGA/DTA/DTG) CPC-CeP were used to characterize the newly synthesized material. The ion-exchange properties were studied through the usual column method. The cation-exchange capacity for CPC-CeP was 2.12 meq g −1 for Na + ions, and optimum concentration for NaNO3 was 1.0 M for complete elution of H + ions. CPC-CeP was found to be more stable thermally and mechanically as compared to CeP. The adsorption studies show that it is selective for Pb 2+ and Cu 2+ ions.